A Comprehensive Review on Stability Analysis of Hybrid Energy System - Namita Kumari; Binh Tran; Ankush Sharma; Damminda Alahakoon (Sensors)
Hybrid Energy Systems (HES) are pivotal in modern power systems. They incorporate conventional and renewable energy sources, energy storage, and main grids to deliver reliable and sustainable power. To ensure the smooth functioning of such systems, stability analysis is essential, particularly in dynamic and unpredictable situations. Despite tremendous progress, the stability analysis of HES is still complex due to challenges such as nonlinearity, system complexity, and uncertainty in renewable energy generation. A thorough understanding of stability analysis for HES is crucial to ensure the reliable and efficient design of these complex power systems. Particularly in the current data-intensive era, vast volumes of data are being collected through advanced sensors and communication technologies. However, no thorough and organised discussion of every facet of HES stability analysis is available in the literature. This paper aims to review various types and techniques for analysing frequency, transient, small-signal, and converter-driven stability, and to assess the importance and challenges of such analyses for HES. By emphasising the need for innovative approaches for stability enhancement, the paper also discusses the importance of continued research in optimising the operation and reliability of hybrid energy systems.